Repent for Alwisia repens: emended descriptions of two species of Alwisia (Myxomycetes) thought to lack a capillitium - Lloyd, Sarah J.; Leontyev, Dmytro; Vigus, Paula; Schnittler, Martin (Phytotaxa, 2024)
The examination of new collections of Alwisia repens and the isotypes of A. repens and A. morula has revealed that these species exhibit a vestigial capillitium in the form of smooth tubules. These tubules are either directed downward or embedded parallel to the peridium; in A. morula they may be long enough to extend from the top to the base of the sporotheca. In both species the upper part of the peridium dehisces into polygonal platelets, which are delimited by preformed fissures. This type of sporotheca opening has not been documented in the Reticulariales before and is known to occur only in certain species within Echinosteliales, Liceales and Trichiales. Newly obtained specimens of A. repens display well-developed, erect stalks. This contradicts the original diagnosis which describes the species as having creeping stalks. We propose emended descriptions for A. repens and A. morula to incorporate these newly discovered characteristics.